2018
DOI: 10.1186/s12939-018-0782-4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to HIV testing among male clients of female sex workers in Indonesia

Abstract: BackgroundFrequent engagement of men in sexual encounters with female sex workers (FSWs) without using condoms places them at a high risk for HIV infection. HIV testing has been noted to be among important strategies to prevent HIV transmission and acquisition. However, it is known that not all men willingly undertake an HIV test as a way to prevent HIV transmission and/or acquisition. This study aimed to identify barriers to accessing HIV testing services among men who are clients of FSWs (clients) in Belu an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 43 publications
3
25
0
5
Order By: Relevance
“…The findings of this study, consistent with the findings of other studies conducted in resource-limited settings, revealed that, given the many barriers associated with HIV testing in a clinic setting, more men preferred to engage themselves with HIV testing services that were conducted outside this setting [16,[46][47][48][49][50][51]. In addition to that, the HIVST model further empowers young people and sexually active individuals to be independent and have the option to choose the location and timing of the test and to control the disclosure of their results [36].…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this study, consistent with the findings of other studies conducted in resource-limited settings, revealed that, given the many barriers associated with HIV testing in a clinic setting, more men preferred to engage themselves with HIV testing services that were conducted outside this setting [16,[46][47][48][49][50][51]. In addition to that, the HIVST model further empowers young people and sexually active individuals to be independent and have the option to choose the location and timing of the test and to control the disclosure of their results [36].…”
Section: Discussionsupporting
confidence: 89%
“…Kasus HIV / AIDS didunia mencapai 39,4 juta orang yang dikelompokkan menjadi kelompok dewasa sebanyak 37,2 juta orang, dan anakanak dibawah usia 15 tahun sebanyak 2,3 juta orang (KemenkesRI, 2007 (Fauk et al, 2018). Selanjutnya penelitian lainnya menemukan bahwa tidak ada hubungan antara umur dengan tingkat pengetahuan remaja tentang HIV/AIDS (p = 0,591 pada alfa 0,05) namun terdapat hubungan yang bermakna antara jenis kelamin dengan tingkat pengetahuan remaja tentang HIV/AIDS dengan p = 0,010 pada alfa 0,05.…”
Section: Pendahuluanunclassified
“…A global report has noted that there are around 8.1 million people living with HIV/AIDS (PLWH) who are not aware of their HIV status [ 93 ], many of them are men [ 94 ]; lower testing coverage among men, compared to women, has also been emphasized by the WHO [ 95 ]. Several studies reveal that the low HIV testing rates among this group [ 89 , 96 ] is due to many reasons, including resistance to being seen at the VCT clinic [ 97 ], logistical issues [ 96 ], low levels of knowledge about HIV and HIV testing [ 98 ], self-perception of being at low HIV risk [ 99 ], and concerns about confidentiality in the event of a positive test result [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reveal that the low HIV testing rates among this group [89,96] is due to many reasons, including resistance to being seen at the VCT clinic [97], logistical issues [96], low levels of knowledge about HIV and HIV testing [98], self-perception of being at low HIV risk [99], and concerns about confidentiality in the event of a positive test result [99].…”
Section: Plos Onementioning
confidence: 99%